Continuing the Journey of Education, Training and Research - Pradhan Shrestha, Basanti Roshan (Journal of Training and Development, 2021)
Issue 6, Volume 6 of the Journal of Training and Development has been published with the objectives of sharing the recent research findings in the field of Technical Vocational Education and Training (TVET) in research, training and development. This publication has a collection of valuable articles from TVET experts, scholars and educationalist. This training and development journals are considered to be valuable resources for the scholars, educationist and TVET experts and stakeholders. This issue consists of seven articles on different aspects of Training and Development. The first article by Jiwak Raj Bajrachrya examines the existing models and framework that has been used to integrate technology into Teaching and Training (2Ts). As described in numerous literatures, currently instructors use TPACK, SMAR, and TPACK-based ID models such as TPACK-COPR model, TPACK-IDDIRR1 model, and TPACK-IDDIRR2 model to achieve the specific goal of an effective 2Ts. He highlighted a few hurdles found in the empirical-based studies in the above-mentioned models and framework and how those hurdles could be alleviated by addressing an extraneous cognitive load of an instructors carrying out technology integration as well as future recommendations for research. The article by Rajendra Bahadur Shrestha highlights the current situation, discovers issues, and share some feasible initiations of employer engagement in the TVET programme. The involvement of employer in TVET system is important to ensure the TVET is demand-driven, quality oriented, future focused and provides skills workers who contributes to the economy’s growth. It also assists to develop responsive labour market skill needs, training design and development, training delivery and post training support. Employer involvement in TVET programs has long been a priority in many nations, however in Nepal, employer involvement in training delivery of TVET programme is under-explored. The article by Thakur Prasad Bhatta aims to explore the governing issue of TVET in the framework of Nepal’s federal government. He focuses on qualitative research approach in scrutinizing policy and practice of TVET in Nepal. This paper explores how the process of governing TVET in Nepal has remained highly centralized despite the rhetoric of decentralization as the main agenda of regulating development over the decades. Arguably, there is a reluctant tendency in devolving TVET as per the new structure of federal governance. Instead, like in other development sectors, disputes between the three levels of government – federal, provincial, and local – are emerging in the case of TVET. He concludes the paper by drawing insights on the federal form of TVET governance. The article by Dr. Prakash C. Bhattarai, Durga Prasad Baral and Prakash Kumar Paudel focus on establishing a TVET fund and sketches the possible alternative approaches with a reformed TVET structure. The literature review focuses on international practices of implementing TVET fund. In addition, the authors have collected opinions from TVET stakeholders on the establishment of a TVET fund in Nepal and based on the findings, they have proposed five possible models for TVET fund mechanism in Nepal. They revealed that all the models have their strengths and challenges, so it would be rational to adopt the idea of strengthening an existing structure rather than attempting to make it stand alone. Its effective implementation requires strong research and innovation, an effective implementing body and an independent quality assurance and accreditation system. The instructors of TECS schools and their perspectives of profession is discussed by Bikash Ghaju, and Dr. Prakash C. Bhattarai. The authors focused to comprehend the experience of TECS instructors on their teaching profession. The narrative inquiry approach was utilized to study the cases in-depth for which four instructors from the Diploma in Civil Engineering program of two TECSs were purposively selected. The paper concludes that while instructors are interested in the teaching profession which assists in career growth but they are unwilling to work at remote TECS schools due to limited career advancement and earning opportunities. Mobile technology has brought about innovative changes in all aspects of life, including interpersonal communication, the economics, and teaching and learning.. Shesha Kanta Pangeni discusses the use of android mobile in education institute of Nepal. His paper is based on the persistence of encouraging the Mobile App for e-learning, which subsidizes access to e-learning resources and prompt communication for learning activities. He collected data through online survey, informal interaction and interview. He discovered that although the facilitators rarely used Mobile App, students used the Mobile App and they wanted the updated version with more user-friendly interface. He summarized that the responsibilities of institutions and facilitators are critical in creating and providing mobile-friendly learning options, and that the success of App use is dependent on facilitators' active role in technology learning facilitation. Devendra Adhikari explores the life experiences of workers in the construction-sector during and after the COVID-pandemic. He implements a qualitative approach under the socio-constructionism paradigm and selected three participants from different sectors masonry, house-painting, and plumbing for in-depth interviews. He discovers that the COVID-pandemic has brought new resilient strategies in the lives of the construction workers such as maintaining high concern for personal safety and the well-being of their families and exploring employment opportunities of the construction sector. Finally, the editorial team wishes to convey their profound gratitude to all of the authors who have contributed by sharing their relevant and significant creations. We would also like to express gratitude to the reviewers and TITI management team for their continuous support in publishing this journal. The team would also like to welcome articles from TVET experts, trainers and stakeholders in the field of training, development and research. We are also grateful to Tribhuvan University Central Library (TUCL) for providing their professionals support and encouragement to publish this journal online. Last but not least, we are thankful to the publisher for the publication of the print version of this journal.